128k views
4 votes
Implement switching function F (A, B, C) = ABC + BC + AB with a 4-to-1 multiplexer: show your assignment A, B, C. to data inputs (D3, D2, D1, D0) and select inputs (S1, S0) of the 4-to-1 multiplexer. A single inverter is available if needed. Obtain the circuit schematic using the 4-to-1 mux and inverter as building blocks.

User Kemal
by
4.7k points

1 Answer

4 votes

Answer:

Step-by-step explanation:


\mathbf{F(A, B, C) = \bar A \bar B C + B \bar C + AB}


\mathbf{F(A, B, C) = \bar A \bar B C + AB \bar C + \bar A B \bar C + ABC + AB \bar C}


\mathbf{F(A, B, C) = 001,110,010,111,110}

Hence;


\mathbf{F(A, B, C) = \sum m (1,2,6.7)}


\mathbf{ A \ \ \ B \ \ \ C \ \ \ \ \ \ \ F } \\ \\ \mathbf{ 0 \ \ \ \ 0 \ \ \ \ 0 \ \ \ \ \ \ \ 0 } \\ \\ \mathbf{ 0 \ \ \ \ 0 \ \ \ \ 1 \ \ \ \ \ \ \ 1 }\to \ \ D_0 = C \\ \\ \mathbf{ 0 \ \ \ \ 1 \ \ \ \ 0 \ \ \ \ \ \ \ 1 } \to \ \ D_1 = \bar C \\ \\ \mathbf{ 0 \ \ \ \ 1 \ \ \ \ 1 \ \ \ \ \ \ \ 0 } \\ \\ \mathbf{ 1 \ \ \ \ 0 \ \ \ \ 0 \ \ \ \ \ \ \ 0 } \\ \\ \mathbf{ 1 \ \ \ \ 0 \ \ \ \ 1 \ \ \ \ \ \ \ 0 }


\\ \\ \mathbf{ 1 \ \ \ \ 1 \ \ \ \ 0 \ \ \ \ \ \ \ 0 } \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \to D_3 = 1 \ \ ; D_2 = 0 \\ \\ \mathbf{ 1 \ \ \ \ 1 \ \ \ \ 1 \ \ \ \ \ \ \ 1 }

The 4-to-1 MUX and inverter is shown in the attached file below.

Implement switching function F (A, B, C) = ABC + BC + AB with a 4-to-1 multiplexer-example-1
User Tzik
by
4.6k points